Análise sobre o Programa Diretor de Turma no Ceará - Morais, Tuíro Camboim (2019)
The main objective of this study is to assess the impact of the Class Director Teacher Project (PPDT) on learning outcomes, student retention, and progression in Ceará. This project is inspired by the Portuguese teaching experience, which, according to Oliveira (2017, p. 17 apud Sá, 1997, p. 46), underwent a phase of expanding enrollment in its education system starting in 1956, during which quality declined in favor of quantity. In this context, the Class Director Teacher Project was implemented in Portugal in 1968 to enable teachers to play a key role in classroom management and learning by monitoring student progress, managing classroom conflicts, and serving as a bridge between students, other teachers, school administrators, families, and the broader school community (Costa, 2014). This project was introduced by the Ceará State Department of Education in 2008, initially as a pilot program in 25 State Schools of Professional Education. It is currently present in more than 639 schools and remains open for additional schools to adopt its framework. The project’s key differentiator is its approach to ensuring that teachers view students holistically - both socially and collectively - but also as individuals. This fosters closer teacher-student relationships, allowing teachers to act as educators of both reason and emotion, aiming to reduce the massification of education. According to Andrade (2009), Barros (2015), and Primi (2015), teaching models that incorporate mentoring practices and socio-emotional skill development through teachers have significant positive impacts on student learning, producing results that are up to 40% greater than strictly pedagogical interventions. So, what is the actual contribuition of the Class Director Teacher Project in student success and retention in Ceará’s schools? This study is descriptive, as it explores the characteristics and history of the project’s implementation in Ceará and its origins in Portugal. It is also quantitative, as it includes econometric analysis to measure the project’s actual impact. Additionally, it is investigative, as it reviews relevant literature on public policy evaluation and educational models focused on mentoring and socio-emotional learning, along with their outcomes. The evaluation of public policies has gained relevance in academia and among public administrators when making decisions, especially within the framework of New Public Management, which prioritizes results, citizen satisfaction, and efficient resource management. Thus, this study brings academic innovation by quantitatively assessing the PPDT, offering valuable contributions to the economics of education and paving the way for further research on public policy evaluation and the Class Director Teacher Project. This study allows for a greater understanding of PPDT, its methodological aspects and and its achieved outcomes. The project’s contribution was observed in terms of the objectives it intends to achieve, qualifying it as an effective public policy, that should be prioritized in the educational policy context of the state.